A new species of Hechtia (Bromeliaceae: Hechtioideae) from Hidalgo (Mexico) - Ramírez, Ivón M.; Hornung-Leoni, Claudia; González, Manuel; Treviño-Carreon, Jacinto (Phytotaxa, 2015)
We propose that two populations previously referred to Hechtia epigyna, from the Mexican state of Hidalgo, represent a new species. Plants from the Hidalgo populations share the inferior ovary with Hechtia epigyna, an unusual trait in the genus, but they differ in their growth pattern (central vs. lateral inflorescence), characters of the adaxial foliar surface, petal color, and fruit position during dehiscence. We also provide a clarification on the typification of Hechtia epigyna. An assessment of the conservation status of the new species, Hechtia deceptrix following IUCN criteria resulted as CR (Critically Endangered).